Improved Yield and Photosynthate Partitioning in AVP1 Expressing Wheat (Triticum aestivum) Plants - Regmi, Kamesh C.; Yogendra, Kalenahalli; Farias, Júlia Gomes; Li, Lin; Kandel, Raju; Yadav, Umesh P.; Sha, Shengbo; Trittermann, Christine; Short, Laura; George, Jessey; Evers, John; Plett, Darren; et al. (Frontiers in Plant Science, 2020)
A fundamental factor to improve crop productivity involves the optimization of reduced carbon translocation from source to sink tissues. Here, we present data consistent with the positive effect that the expression of the Arabidopsis thaliana H+-PPase (AVP1) has on reduced carbon partitioning and yield increases in wheat. Immunohistochemical localization of H+-PPases (TaVP) in spring wheat Bobwhite L. revealed the presence of this conserved enzyme in wheat vasculature and sink tissues. Of note, immunogold imaging showed a plasma membrane localization of TaVP in sieve element- companion cell complexes of Bobwhite source leaves. These data together with the distribution patterns of a fluorescent tracer and [U14C]-sucrose are consistent with an apoplasmic phloem-loading model in wheat. Interestingly, 14C-labeling experiments provided evidence for enhanced carbon partitioning between shoots and roots, and between flag leaves and milk stage kernels in AVP1 expressing Bobwhite lines. In keeping, there is a significant yield improvement triggered by the expression of AVP1 in these lines. Green house and field grown transgenic wheat expressing AVP1 also produced higher grain yield and number of seeds per plant, and exhibited an increase in root biomass when compared to null segregants. Another agriculturally desirable phenotype showed by AVP1 Bobwhite plants is a robust establishment of seedlings.